Error Analysis of Simple Present Tense in Descriptive Text - Muniroh, Zumrotul; Dwiastuty, Nina; Miranti, Ira (JEdu: Journal of English Education, 2024)
This research aims to find errors in using the simple present tense structure that are often made by employees when writing descriptive essays in English. The method used is descriptive qualitative with descriptive qualitative techniques. From this research, results were obtained in the form of simple present tense structure errors by employees of Bank Central Asia, Bumi Permata branch in writing descriptive essays. These errors were in the form of misformation errors, namely 54.76%, followed by omission errors at 27.00%, then error of addition at 14.28%, while the type of error that was least committed was error of misordering at 3.96%. The most common mistakes made are errors of misformation, where employees make mistakes in choosing the right vocabulary, verbs and also to be.